Statistical methods and algorithms for spatio-temporal cluster analysis - Abramovich, Mikhail; Mitskevich, Mikhail (Studia Informatica. System and information technology, 2019)
the global clusterization test and scan statistic method for studying geographical distributionof the objects are considered. the algorithm of windows set construction for the flexible spatial wasdeveloped. the robust version of spatial scan statistic method is proposed. the children carcinoma of thebelarus was analyzed using scan statistic method.